QUALITY OF WORK LIFE, PERSONALITY, JOB SATISFACTION, COMPETENCE, AND JOB PERFORMANCE: A CRITICAL REVIEW OF LITERATURE - Muindi, Florence; K’Obonyo, Peter (European Scientific Journal, ESJ, 2015)
The success of any organization is highly dependent on how it attracts recruits, motivates, and retains a high performing workforce. Explaining the factors that influence employee performance remains a fundamental question for human resources management practitioners. The expectancy theories of Vroom, Porter, and Lawler, assert that employee performance depends not only on the amount of effort exerted, but also on the intervening influences of factors such as person’s abilities and traits, as well as their role perceptions. Researchers also suggest that a range of organizational and employee factors could impact employee performance. These include Quality of work life, ability, effort, motivation, attitude, personality, competence, and job satisfaction. This study looked at selected employee related factors, namely: employee personality, job satisfaction, and competence. QWL was included because organizations are known to adopt a strategy for improving employees’ Quality of Work Life (QWL) with the aim of satisfying both the organizational objectives and the needs of the employee. On the other hand, successful organizations consider job satisfaction to be important for work performance. However, job satisfaction alone cannot lead to performance. Having the right competences is important for performance. This review therefore seeks to investigate the employee related factors that influence the relationship between quality of work life and employee’s performance.